PEMBIAYAAN MIKRO DALAM KALANGAN USAHAWAN ASNAF ZAKAT: KAJIAN KES DI MAIDAM, TERENGGANU - Mohd Azamri, Khairunnisa; Ibrahim, Muhammad Anas (Jurnal 'Ulwan, 2024)
This paper aims to examine the distribution of zakat in the form of micro-credit financing from zakat funds that can be implemented by the Majlis Agama Islam dan Adat Istiadat Melayu Terengganu (MAIDAM). The current distribution method is more "one-off". However, it is often misused, or the funds provided lack responsibility from the recipients. Therefore, the distribution of zakat in the form of micro-financing provides shared responsibility to ensure that the distributed funds do not incur losses. The question is, what will happen if the annual zakat collection amount is affected in the future, while the number of asnaf (eligible zakat recipients) continues to increase? Moreover, the provision of working capital in the form of micro-credit currently offered is said not to be free from elements of usury (riba). Data was collected from informants through semi-structured interviews with zakat practitioners and analyzed using content analysis. Findings from primary and secondary data indicate that there are views that allow zakat distribution to be given in the form of micro-credit financing for business capital or additional capital to expand businesses among asnaf entrepreneurs. Suitable contracts to be used include qardu hasan, mudarabah, musyarakah mutanaqisah, and ijara. In addition, reviews on the definition of micro-credit financing, the law of micro-credit financing from zakat funds, and the practice of micro-credit financing from zakat funds in other countries can be used as models to be applied in zakat institutions in Malaysia.